Paciente de sexo masculino de 35 años de edad con obesidad mórbida. - Mata Lara, Solange Mabel (2020)
The present clinical case is about a 35-year-old male patient with morbid obesity, who attended a medical consultation due to vertigo, dizziness on many occasions, tiredness, decreased concentration, easily exhausted and marked palpitations, also smoker 1 cigarette spending a day and alcohol at the end of the month, in his family pathological history he does not refer to news, he refers that since adolescence he has been overweight which increases progressively with the passing of the years, he refers that his food consumption is 5 to 6 times a day , He has onions for breakfast with 5 breads, chifle and cola, before lunch he eats 3 meat cakes, lunch with paw broth, rice with puree and fried meat, orange juice, then eat green tortillas with cola and a snack of rice with stew and chicken fried, he refers that for about 2 months he has suffered from palpitations in the chest, especially when he performs activities such as going up and down stairs. The nutritional evaluation is carried out with anthropometric, biochemical, clinical and dietary indicators, where a body mass index of 43.16kg / m2 is observed, an increase in the percentage of body and visceral fat, within the laboratory tests it shows an alteration of the lipid profile and Transaminases to the limit, and in their intake, they refer to a hypercaloric and hyperlipidic diet by calculating the 24-hour reminder. Through nutritional intervention with the aim of improving the nutritional status of the patient, a hypocaloric diet of 2000 kilocalories is prescribed, divided into 5 meal times, in conclusion through follow-up it is observed that the patient loses weight considerably 4 kg and the percentage of body fat and visceral decreases as well as the biochemical parameters, the dietary plan is maintained for a long time with medical, psychological and nutritional monitoring until reaching the established objective.